Unpacking the Nexus Between CEO Characteristics and Risk-Taking Behavior: A Systematic Literature Review Using the ADO Model - Lam, Nguyen Thanh (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study systematically reviews empirical research on how CEO characteristics influence firm?level risk?taking behavior, applying the Antecedent–Decision–Outcome (ADO) framework to integrate and synthesize heterogeneous findings. Design/methodology/approach – Following PRISMA guidelines, we searched the Scopus database for peer?reviewed articles published between 2000 and 2024. From 1,230 initial records, 34 studies satisfied our inclusion criteria. Each article was coded for antecedents (demographics, professional experience, psychological traits, incentive structures, and structural roles), decisions (strategic risk?taking, financial policies, and operational actions), and outcomes (financial performance, risk metrics, and strategic results). Findings – The evidence demonstrates that a broad array of CEO traits—beyond basic demographics—significantly shape organizational risk?taking choices, which in turn drive firm performance and risk profiles. We identify underexplored antecedents (e.g. religious affiliation, overconfidence), reveal the importance of contextual moderators (governance mechanisms, industry and macroeconomic conditions), and highlight gaps in research on emerging and transitional economies. Originality/value – By explicitly framing the literature through an ADO lens, this review offers a unifying conceptual model that advances Upper Echelons and Behavioral Agency theories. It provides actionable insights for boards, compensation committees, and regulators, while charting a clear agenda for future mixed?methods and longitudinal studies